Propofol sedation with bispectral index monitoring is useful for endoscopic submucosal dissection: a randomized prospective phase II clinical trial - Sasaki, T.; Tanabe, S.; Azuma, M.; Sato, A.; Naruke, A.; Ishido, K.; Katada, C.; Higuchi, K.; Koizumi, W. (Endoscopy, 2012)
Background and study aims: Endoscopic submucosal dissection (ESD) has become a standard treatment. However, the treatment time tends to be relatively long and insufflation and manipulation of the endoscope can increase pain and discomfort. We aimed to find an optimal method for sedation during ESD. Patients and methods: Patients scheduled to undergo ESD for early gastric cancer or adenoma were randomly assigned to sedation with midazolam or propofol, and consciousness level was evaluated by bispectral index (BIS) monitoring. Primary end points of effectiveness (three parameters) and secondary end points of safety during ESD and after return to the ward were compared between the groups. Study registration was in the UMIN Clinical Trial Registry (UMIN 000001497), and the institutional trial number was KDOG 0801.Results: From June 2008 through June 2009, we enrolled 178 patients (90 midazolam, 88 propofol). Regarding safety after ESD, recovery was significantly better in the propofol group immediately after and at 1 hour and 2 hours after return to the ward (P < 0.001). The number of patients who required a continuous supply of oxygen 2 hours after returning to the ward was significantly lower in the propofol group (midazolam 18; propofol 6; P = 0.010). Though propofol seemed to be better for effectiveness and safety, there were no statistically significant differences for all three primary end points and the safety parameters (hypotension, hypoxia, bradycardia).Conclusions: Propofol with BIS monitoring improved recovery of patients after ESD, though this study was underpowered to prove the effectiveness and safety of propofol.